RETRACTED: Effective methods of agricultural use of light colored gray soils distributed in Kuva hill - Askarov Khasanboy; Sulaymonov Omonjon; Mamajonov Ghaybullo; Yigitaliyev Dilmurod; Mirzaikromov Mizabobur; Marufjonov Abdurakhmon (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001